Thermal and Flame Retardant Performance of Glass Fiber-Reinforced UPR Composites Modified with Boric Acid and Sodium Silicate - Kristiawan, Ruben Bayu; Pramudi, Ganjar; Roni, Komar (Universitas Mercu Buana, 2025)
This study investigates the effect of sodium silicate (Na₂SiO₃) and boric acid (BA) as flame-retardant additives in unsaturated polyester resin (UPR) reinforced with E-glass fibres. The fire performance of the composites was evaluated based on varying additive concentrations by % volume fraction, using standardised testing methods in burning rate (BR) with ASTM D 635-22. Results indicate that Na₂SiO₃ contributes to fire resistance by forming a thermally stable, glass-like barrier, while BA proves more effective by interrupting combustion reactions and generating protective boron oxide residue. Notably, the combination of Na₂SiO₃ and BA produced a synergistic effect, resulting in a significant reduction in burning rate. Thermogravimetric analysis (TGA) further confirmed the enhanced thermal stability of the composite, particularly in the NB10 formulation with 2% Na₂SiO₃ and 8% BA, which demonstrated the slowest degradation at elevated temperatures. These findings suggest that optimising the ratio of Na₂SiO₃ and BA yields high-performance, fire-retardant composites suitable for applications demanding superior fire resistance and thermal durability, such as electric vehicle safety components.